Type 1 Interleukin-4 Signaling Obliterates Mouse Astroglia in vivo but Not in vitro - Mashkaryan, Violeta; Siddiqui, Tohid; Popova, Stanislava; Cosacak, Mehmet Ilyas; Bhattarai, Prabesh; Brandt, Kerstin; Govindarajan, Nambirajan; Petzold, Andreas; Reinhardt, Susanne; Dahl, Andreas; Lefort, Roger; Kizil, Caghan (Frontiers in Cell and Developmental Biology, 2020)
Recent findings suggest that reduced neurogenesis could be one of the underlying reasons for the exacerbated neuropathology in humans, thus restoring the neural stem cell proliferation and neurogenesis could help to circumvent some pathological aspects of Alzheimer’s disease. We recently identified Interleukin-4/STAT6 signaling as a neuron-glia crosstalk mechanism that enables glial proliferation and neurogenesis in adult zebrafish brain and 3D cultures of human astroglia, which manifest neurogenic properties. In this study, by using single cell sequencing in the APP/PS1dE9 mouse model of AD, we found that IL4 receptor (Il4r) is not expressed in mouse astroglia and IL4 signaling is not active in these cells. We tested whether activating IL4/STAT6 signaling would enhance cell proliferation and neurogenesis in healthy and disease conditions. Lentivirus-mediated expression of IL4R or constitutively active STAT6V impaired the survival capacity of mouse astroglia in vivo but not in vitro. These results suggest that the adult mouse brain generates a non-permissive environment that dictates a negative effect of IL4 signaling on astroglial survival and neurogenic properties in contrast to zebrafish brains and in vitro mammalian cell cultures. Our findings that IL4R signaling in dentate gyrus (DG) of adult mouse brain impinges on the survival of DG cells implicate an evolutionary mechanism that might underlie the loss of neuroregenerative ability of the brain, which might be utilized for basic and clinical aspects for neurodegenerative diseases.